Theoretical and empirical investigations of divination and magic: manipulating the divine - Sørensen, Jesper; Klostergaard Petersen, Anders (Studies in the history of religions, 2021)
"In Theoretical and Empirical Investigations of Divination and Magic ten leading scholars of religion provide up-to-date investigations into the classic domains of divination and magic. Spanning historical, anthropological, cognitive, philosophical and theoretical chapters, the volume's authors invite the reader to explore how divinatory practices and magical rituals, both apart and in interaction, can be reconceptualized in line with 21st century scholarship. Following an introduction addressing the ever-pertinent discussion of the status and epistemological value of the categories inherited from our scholarly predecessors, the volume includes analyses of divinatory and magic practices in particular historical areas, as well as comparative, theoretical and philosophical discussions, making this an indispensable volume for anyone interested in broader comparative approaches to magic and divination. In Theoretical and Empirical Investigations of Divination and Magic ten leading scholars of religion provide up-to-date investigations into the classic domains of divination and magic. Spanning historical, anthropological, cognitive, philosophical and theoretical chapters, the volume's authors invite the reader to explore how divinatory practices and magical rituals, both apart and in interaction, can be reconceptualized in line with 21st century scholarship. Following an introduction addressing the ever-pertinent discussion of the status and epistemological value of the categories inherited from our scholarly predecessors, the volume includes analyses of divinatory and magic practices in particular historical areas, as well as comparative, theoretical and philosophical discussions, making this an indispensable volume for anyone interested in broader comparative approaches to magic and divination. Contributors are Lars Albinus, Edward Bever, Gideon Bohak, Corby Kelly, Lars Madsen, Anders Klostergaard Petersen, Jörg Rüpke, Jesper Frøkjær Sørensen, Jørgen Podemann Sørensen, Dimitris Xygalatas"--